Learning: Principles and Applications / International Edition - Klein Stephen B (Mcgraw Hill International Editions, 1987)
Preface, Theoretical Approaches to Learning, Pavlovian Conditioning, Instrumental Appetitive Conditioning, Instrumental Aversive Conditioning, Stimulus Control of Behavior, Cognitive Control of Behavior, Complex Learning Tasks, Memory Storages, Memory Retrieval, Biological Influence on Learning, References, Indexes, Name and Subject Index.